A semi-dominant NLR allele causes whole-seedling necrosis in wheat. Issue 1 (11th February 2021) - Jia, Haiyan; Xue, Shulin; Lei, Lei; Fan, Min; Peng, Shuxia; Li, Tian; Nagarajan, Ragupathi; Carver, Brett; Ma, Zhengqiang; Deng, Junpeng; Yan, Liuling
Abstract: Programmed cell death (PCD) and apoptosis have key functions in development and disease resistance in diverse organisms; however, the induction of necrosis remains poorly understood. Here, we identified a semi-dominant mutant allele that causes the necrotic death of the e ntire s eedling (DES) of wheat ( Triticum aestivum L.) in the absence of any pathogen or external stimulus. Positional cloning of the lethal allele mDES1 revealed that this premature death via necrosis was caused by a point mutation from Asp to Asn at amino acid 441 in a nucleotide-binding leucine-rich repeat protein containing nucleotide-binding domain and leucine-rich repeats. The overexpression of mDES1 triggered necrosis and PCD in transgenic plants. However, transgenic wheat harboring truncated wild-type DES1 proteins produced through gene editing that exhibited no significant developmental defects. The point mutation in mDES1 did not cause changes in this protein in the oligomeric state, but mDES1 failed to interact with replication protein A leading to abnormal mitotic cell division. DES1 is an ortholog of Sr35, which recognizes a Puccinia graminis f. sp. tritici stem rust disease effector in wheat, but mDES1 gained function as a direct inducer of plant death. These findings shed light on the intersection of necrosis, apoptosis, and autoimmunity in plants. Abstract : An R-gene in hexaploid wheat causes premature death of the entire seedling in the absence of any pathogen or external stimulus.